Embedded systems: design, analysis and verification : 4th IFIP TC 10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 17-19, 2013. Proceedings - Götz, Marcelo; Rettberg, Achim; Zanella, Mauro C.; Rammig, Franz J.; Schirner, Gunar (IFIP Advances in Information and Communication Technology, 2013)
This book constitutes the refereed proceedings of the 4th IFIP TC 10 International Embedded Systems Symposium, IESS 2013, held in Paderborn, Germany, in June 2013. The 22 full revised papers presented together with 8 short papers were carefully reviewed and selected from 42 submissions. The papers have been organized in the following topical sections: design methodologies; non-functional aspects of embedded systems; verification; performance analysis; real-time systems; embedded system applications; and real-time aspects in distributed systems. The book also includes a special chapter dedicated to BMBF funded ARAMIS project on Automotive, Railway and Avionics Multicore Systems.